Factors affecting unfavourable results from a sinonasal inverted papilloma surgery - Anan Bedavanija (2020)
© 2020 Faculty of Medicine Siriraj Hospital, Mahidol University. Objective: Sinonasal inverted papilloma (SNIP) is the most common nasal benign tumor, but locally invasive. The standard treatment is to identify origins of the tumor and total removal. Unfavourable results are finding postoperative residual or recurrent tumors. The aim of this study is to determine factors affecting postoperative residual or recurrent tumors and a rate of getting postoperative residual or recurrent tumors from SNIP surgeries. Methods: A retrospective study in patients with SNIPs was conducted. Relationships between demographic data, tumor sites, tumor stages by Krouse classification, surgical approaches, surgeons' experience, using microdebrider assisted surgery, operative time, intraoperative blood loss, histopathology, Epstein Barr virus (EBV), human papillomavirus (HPV) infection, time to detect tumor after surgery and unfavourable results were evaluated. HPV and EBV were detected by in situ hybridization. Results: 73 patients were included in this study. Unfavourable results were found in 27 patients (36.99%). 50% of patients received unfavourable results after postoperative duration of 115 months. 5 years of a disease-free survival rate was 64.3% (95% CI: 51.9% to 76.7%). The patients with external surgical approaches got worse results than those with endoscopic sinus surgery (p = 0.01, a hazard ratio of 3.88, 95% CI: 1.39 to 10.87). The patients operated without using microdebrider assisted surgery got worse results than those with using the device (p < 0.001, an adjusted hazard ratio of 5.09, 95% CI: 2.08 to 12.45). The patients with abnormal pathological changes (tissue dysplasia and malignant transformation) had worse results than those without changes (p = 0.02, an adjusted hazard ratio of 3.42, 95% CI: 1.24 to 9.38). Conclusion: Non-endoscopic nasal surgery, non-using microdebrider assisted surgery, and abnormal pathological changes may be some of the causes of unfavourable results from SNIP surgeries. Long postsurgical surveillance should be done, because of 36.99% of patients received unfavourable results from SNIP surgeries.